Alterations in lipidome profiles distinguish early-onset hyperuricemia, gout, and the effect of urate-lowering treatment - Kvasnička, Aleš; Friedecký, David; Brumarová, Radana; Pavlíková, Markéta; Pavelcová, Kateřina; Mašínová, Jana; Hasíková, Lenka; Závada, Jakub; Pavelka, Karel; Ješina, Pavel; Stibůrková, Blanka (Arthritis research & therapy, 2023)
BACKGROUND: Currently, it is not possible to predict whether patients with hyperuricemia (HUA) will develop gout and how this progression may be affected by urate-lowering treatment (ULT). Our study aimed to evaluate differences in plasma lipidome between patients with asymptomatic HUA detected ≤ 40 years (HUA ≤ 40) and > 40 years, gout patients with disease onset ≤ 40 years (Gout ≤ 40) and > 40 years, and normouricemic healthy controls (HC). METHODS: Plasma samples were collected from 94 asymptomatic HUA (77% HUA ≤ 40) subjects, 196 gout patients (59% Gout ≤ 40), and 53 HC. A comprehensive targeted lipidomic analysis was performed to semi-quantify 608 lipids in plasma. Univariate and multivariate statistics and advanced visualizations were applied. RESULTS: Both HUA and gout patients showed alterations in lipid profiles with the most significant upregulation of phosphatidylethanolamines and downregulation of lysophosphatidylcholine plasmalogens/plasmanyls. More profound changes were observed in HUA ≤ 40 and Gout ≤ 40 without ULT. Multivariate statistics differentiated HUA ≤ 40 and Gout ≤ 40 groups from HC with an overall accuracy of > 95%. CONCLUSION: Alterations in the lipidome of HUA and Gout patients show a significant impact on lipid metabolism. The most significant glycerophospholipid dysregulation was found in HUA ≤ 40 and Gout ≤ 40 patients, together with a correction of this imbalance with ULT.
Keywords: Gout; Humans; hyperurikemie; Lipidomics; Glycerophospholipids; antiuratika; Uric Acid; lipidomika; kyselina močová; dna (nemoc); LC–MS; Urate-lowering treatment; lidé; Hyperuricemia; Gout Suppressants